A magnetic resonance imaging framework for quantifying intervertebral disc deformation in vivo: Reliability and application to diurnal variations in lumbar disc shape. (11th April 2018) - Martin, John T.; Oldweiler, Alexander B.; Spritzer, Charles E.; Soher, Brian J.; Erickson, Melissa M.; Goode, Adam P.; DeFrate, Louis E.
Abstract: Low back pain is a significant socioeconomic burden in the United States and lumbar intervertebral disc degeneration is frequently implicated as a cause. The discs play an important mechanical role in the spine, yet the relationship between disc function and back pain is poorly defined. The objective of this work was to develop a technique using magnetic resonance imaging (MRI) and three-dimensional modeling to measure in vivo disc deformations. Using this method, we found that disc geometry was measurable with precision less than the in-plane dimensions of a voxel (≈100 µm, 10% of the MRI pixel size). Furthermore, there was excellent agreement between mean disc height, disc perimeter, disc volume and regional disc height measurements for multiple trials from an individual rater (standard deviation <3.1% across all measurements) and between mean height, perimeter, and volume measurements made by two independent raters (error <1.5% across all measurements). We then used this measurement system to track diurnal deformations in the L5-S1 disc in a young, healthy population (n = 8; age 24.1 ± 3.3 yrs; 2 M/6F). We measured decreases in the mean disc height (−8%) and volume (−9%) with no changes in perimeter over an eight-hour workday. We found that the largest height losses occurred in the posterior (−13%) and posterior-lateral (−14%) regions adjacent to the outer annulus fibrosus. Diurnal annulus fibrosus (AF) strains induced by posterior and posterior-lateral height loss may increase the risk for posterior disc herniation or posterior AF tears. These preliminary findings lay a foundation for determining how deviations from normal deformations may contribute to back pain.